Increase Purchasing Decision With Social Media Marketing and Corporate Social Responsbility (Case Study at Product TDRIVE PT Asuransi Tugu Pratama Indonesia) - Rangga, Yongky; Agung, Novan Ridho (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
This research aims to determine the influence of the relationship between Social Media Marketing and Corporate Social Responsibility on Purchasing Decisions with Brand Image as an intervening variable and Brand Trust as a moderating variable. The type of research used in this research is descriptive quantitative research. The population in this study were users of PT Asuransi Tugu Pratama Indonesia's Tdrive product. The sampling technique used was purposive sampling. The number of samples in this study was 270 samples. The data analysis method in this research is using Structural Equation Modeling (SEM) with SmartPLS 4. The results of the research show that Social media marketing has no effect on purchasing decisions, Corporate social responsibility has a positive and significant effect on purchasing decisions, Social media marketing has a positive and significant effect on brand image, corporate social responsibility has a positive and significant effect on brand image, brand image has a positive and significant effect on purchasing decisions, and brand image is able to mediate the relationship between corporate social responsibility on purchasing decisions and brand trust is not able to moderate the relationship between social media marketing and decisions. purchase.